Differential Effects of D-Cycloserine and ACBC at NMDA Receptors in the Rat Entorhinal Cortex Are Related to Efficacy at the Co-Agonist Binding Site. - Alex M Lench; Emma Robson; Roland S G Jones (PLoS ONE, 2015)
Partial agonists at the NMDA receptor co-agonist binding site may have potential therapeutic efficacy in a number of cognitive and neurological conditions. The entorhinal cortex is a key brain area in spatial memory and cognitive processing. At synapses in the entorhinal cortex, NMDA receptors not only mediate postsynaptic excitation but are expressed in presynaptic terminals where they tonically facilitate glutamate release. In a previous study we showed that the co-agonist binding site of the presynaptic NMDA receptor is endogenously and tonically activated by D-serine released from astrocytes. In this study we determined the effects of two co-agonist site partial agonists on both presynaptic and postsynaptic NMDA receptors in layer II of the entorhinal cortex. The high efficacy partial agonist, D-cycloserine, decreased the decay time of postsynaptic NMDA receptor mediated currents evoked by electrical stimulation, but had no effect on amplitude or other kinetic parameters. In contrast, a lower efficacy partial agonist, 1-aminocyclobutane-1-carboxylic acid, decreased decay time to a greater extent than D-cycloserine, and also reduced the peak amplitude of the evoked NMDA receptor mediated postsynaptic responses. Presynaptic NMDA receptors, (monitored indirectly by effects on the frequency of AMPA receptor mediated spontaneous excitatory currents) were unaffected by D-cycloserine, but were reduced in effectiveness by 1-aminocyclobutane-1-carboxylic acid. We discuss these results in the context of the effect of endogenous regulation of the NMDA receptor co-agonist site on receptor gating and the potential therapeutic implications for cognitive disorders.